FORMULATION AND EVALUATION OF FLOATING BIOADHESIVE TABLETS OF ONDANSETRON - SHUBHRAJIT MANTRY; G. NARESH KUMAR; K. VENKATA NARAPA REDDY; JANJIRALA DEVENDAR (International Journal of Pharma and Bio Sciences, 2013)
The aim of present work was to formulate, evaluate and optimize gastro-retentive tablet of Ondansetron HCl which would be advantageous, that can provide prolong gastric retention and increase efficacy of the dosage form. The objective of the present study is to developed a Floating bioadhesive tablets of Ondansetron hydrochloride. Systematic studies were conducted using different concentration of rate releasing polymer HPMC and Sodium carboxy methyl cellulose for extending the drug release in upper GIT. Preformulation studies were done to find the micromeritic properties to assess flow ability, compressibility. All the formulations gave good results for above studies. Formulated tablets gave satisfactory results for various physical tablet evaluation parameters like tablet dimensions, hardness, friability, weight variation, buoyancy, content uniformity, all the formulations were found within the permissible range.